2020
DOI: 10.1097/prs.0000000000006375
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Skills Acquisition by Plastic Surgery Residents through Digital Simulation Training: A Prospective, Randomized, Blinded Trial

Abstract: Background: Simulation is a standard component of residency training in many surgical subspecialties, yet its impact on knowledge and skills acquisition in plastic surgery training remains poorly defined. The authors evaluated the potential benefits of simulation-based cleft surgery learning in plastic surgery resident education through a prospective, randomized, blinded trial. Methods: Thirteen plastic surgery residents were randomized to a digital sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…In a blinded study, it yielded superior results when compared with those in traditional training. 43 …”
Section: Simulation In Craniofacial Surgerymentioning
confidence: 99%
“…In a blinded study, it yielded superior results when compared with those in traditional training. 43 …”
Section: Simulation In Craniofacial Surgerymentioning
confidence: 99%
“… 4 , 7 , 8 This focal deficit is likely due, at least in part, to a more complicated operating process and the highly sensitive and visible nature of facial outcomes. 33 , 34 In addition, the ACGME-mandated minimum number of nonsurgical cases, namely botulinum toxin injections and dermal fillers, have been difficult to reach for many residents. 30 Although these procedures should be performed with less time commitment and training than with more complex surgeries, residents are suffering from a lack of confidence and a suboptimal level of patient demand, which makes gaining experience difficult.…”
Section: Resident and Attending Physician Perspectivesmentioning
confidence: 99%
“… 31 , 32 In addition, studies have shown that simulation-based training produces more significant increases in both knowledge and skill when compared with more traditional educational methods, including self-directed reading and the use of digital images. 33 , 34 Simulation training includes use of cadavers, animal models, and prosthetic devices. Simulation training has been used in other subspecialties of plastic surgery, most notably with animal models for microsurgical vessel anastomosis training and human cadaver models for popular flap reconstruction courses.…”
Section: Simulation In Aesthetic Trainingmentioning
confidence: 99%
“…Online modules for training, simulation, and virtual learning through smart technology apps continue to rapidly expand within plastic surgery education. 20 25 …”
Section: Looking Back: Pre–covid-19mentioning
confidence: 99%